DA CIDADE À NATUREZA: DIRETRIZES PARA INTEGRAR INFRAESTRUTURA VERDE EM CANTEIROS CENTRAIS EM CAMPO GRANDE - MS - Antonio de Jesus Nazareth Neto (2024)
Green Infrastructure (GI) has emerged as an essential component in urban transformation, addressing challenges such as climate change, biodiversity loss, and landscape degradation. Between 2013 and 2023, academic interest in GI grew significantly, with a 22.20% annual increase in scientific literature, as evidenced by the analysis of 4,395 articles. This research focused on the central flowerbeds of Campo Grande, MS, underscoring the need for public policies to ensure a more equitable distribution of green spaces. The study employed methodologies such as georeferencing and supervised classification to analyze vegetation cover and identify impervious surfaces in central flowerbeds. Furthermore, specific guidelines were developed for the implementation of GI in these areas, aiming to expand vegetation cover, increase biodiversity, optimize stormwater management, integrate GI with urban mobility, and promote community engagement and environmental education. Significant variations in the distribution of green areas were observed, revealing inequalities in urban planning that directly impact quality of life and urban biodiversity. The importance of expanding inclusive policies for green cover, especially in underinvested areas, is emphasized. The developed guidelines stress the integration of natural elements into urban planning to mitigate the negative effects of urbanization on the landscape, promoting more sustainable and climate-resilient development. The specific objectives include: structuring a current overview of GI publications, evaluating conceptual aspects and scientific productions; assessing the landscape characteristics of Campo Grande's central flowerbeds from an urbanistic perspective, including vegetation cover composition and ecosystem services; and developing guidelines for implementing green infrastructure in urban central flowerbeds. This dissertation expanded the theoretical and practical understanding of green infrastructure, proposing that central flowerbeds be reimagined as elements of sustainable urban infrastructure, beyond mere traffic dividers.